Rutin mitigates hepatic fibrogenesis and inflammation through targeting TLR4 and P2X7 receptor signaling pathway in vitro and in vivo. (January 2020) - Hou, Li-Shuang; Cui, Zhen-Yu; Sun, Peng; Piao, Hui-Qing; Han, Xin; Song, Jian; Wang, Ge; Zheng, Shuang; Dong, Xiu-Xiu; Gao, Lu; Zhu, Yue; Lian, Li-Hua; et al.
Graphical abstract: Highlights: Rutin mitigates hepatic fibrogenesis via TLR4-P2X7r signaling. Rutin decreases fibrosis markers in activated HSCs via suppressing TLR4. Rutin protects primary hepatocytes via blocking TLR4-P2X7r. Abstract: Rutin is a flavonol glycoside widely existing in plants, used as food antioxidant and nutritional enhancer. Rutin has vitamin P-like effect and anti-inflammatory effect. This study aims to investigate the effects and potential mechanisms of rutin against hepatic fibrosis in vivo and in vitro . The present study found that rutin significantly decreased fibrosis markers, and TLR4, IRAK4, P2X7r/NLRP3 signaling pathway in activated HSCs, as well as functioning as TLR4 inhibitor. In primary hepatocytes, rutin also inhibited TLR4-IRAK-P2X7r signaling pathway underlying TGF-β stimulation. In TAA-induced mice, rutin could attenuate the histopathological changes, fibrosis markers, and inflammatory factor. Rutin also suppressed TLRs, IL-1 receptor associated kinase, P2X7r, and NLRP3 expressions. Activation of TLRs/P2X7r signaling is required for HSCs activation, contributing to hepatic fibrosis in mice. Rutin exhibited a protective effect against hepatic fibrosis at least partly through suppressing TLR4 and P2X7r signaling.